Understanding How Headings Influence Text Processing - Julie Lemarié; Robert F. Lorch Jr.; Marie-Paule Péry-Woodley (Discours)
Titles and headings are commonly used signaling devices in expository texts. Researchers in cognitive and educational psychology have demonstrated several important effects of headings and titles on text processing: headings improve memory for text organization; headings influence text comprehension by activating readers’ prior knowledge; and titles can bias text comprehension by their emphasis on a particular text topic. However, the lack of precise linguistic analyses of titles/headings has limited both the scope of empirical research and the precision of conclusions. We present a theory of signaling devices that provides a detailed analysis of variation in titles and headings and generates predictions concerning their effects. We discuss the implications of our analyses for research on titles and headings and summarize recent research findings that illustrate the validity of a central component of our analyses. Finally, we propose some future research directions integrating insights from linguistics for the study of how headings and titles affect text processing.